2014
DOI: 10.1117/12.2048278
|View full text |Cite
|
Sign up to set email alerts
|

Critical assessment of the transport of intensity equation as a phase recovery technique in optical lithography

Abstract: Photomasks are expected to have phase effects near edges due to their 3D topography, which can be modeled as imaginary boundary layers in thin mask simulations. We apply a modified transport of intensity (TIE) phase imaging technique to through-focus aerial images of photomasks in order to recover polarization-dependent edge effects. We use AIMS measurements with 193nm light to study the dependence of recovered phase on mask type and geometry. The TIE is an intensity conservation equation that quantitatively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Note that although the TIE equation is based on the paraxial approximation, it is justified for the mask-side NA of 0.3375 in the experiments here. More details on the experimental setup can be found in [23]. Images of the experimentally recovered phase are shown in Fig.…”
Section: J4mentioning
confidence: 99%
See 3 more Smart Citations
“…Note that although the TIE equation is based on the paraxial approximation, it is justified for the mask-side NA of 0.3375 in the experiments here. More details on the experimental setup can be found in [23]. Images of the experimentally recovered phase are shown in Fig.…”
Section: J4mentioning
confidence: 99%
“…We then propose an iterative wrapper for the traditional TIE solver that corrects such errors to produce a more accurate phase result. This method was first described in [23,24] and later appeared in [25]. We further derive how the curl component is coupled into the intensity measurements, and show that our proposed method also recovers part of the missing curl.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work, 3 using experimental images of an OMOG absorber taken with AIMS T M (Aerial Imaging Measurement System 4 ), the wafer phase across a feature was obtained from a through-focus intensity stack by solving the Transport of Intensity Equation (TIE) . 5,6 It was observed that significant phase modulation does exist across the absorber, especially when illumination polarization is perpendicular to the feature edge (TM), seen in Fig.…”
Section: Introductionmentioning
confidence: 99%